Islamic Schools and Social Justice in Indonesia: A Student Perspective - Raihani, R. (Al-Jamiah Research Centre, Sunan Kalijaga State Islamic University, 2012)
The study explores how students of two different Islamic Senior Secondary Schools in Palangkaraya, Indonesia experience school practices in regards to social justice. Employing a qualitative approach, the researcher conducted ethnographic observations of the schoolsâ practices and events, and interviewed more than fifty students of the two schools individually and in groups to understand their feelings and perspectives about how the schools promote social justice among them. The findings suggest that several school structures including the subject stream selection, student groupings, the emergence of the model or international classroom were found to have been sources for social injustice. Students of the Social Sciences and Language groups, of low academic performance and economically disadvantaged admitted the feeling of unfair treatment because of this structuration. Confirming the theory of social reproduction, the schools failed to provide distributive, cultural and associational justices, and reasserted further inequalities among members of society.[Artikel ini menjelaskan bagaimana siswa pada dua Sekolah Menengah Atas di Palangkaraya, Indonesia merasakan praktik pendidikan di sekolah mereka, khususnya terkait dengan masalah keadilan sosial. Melalui studi kualitatif, penulis melakukan observasi etnografis terhadap praktik pendidikan dan kegiatan sekolah serta melakukan wawancara dengan lebih dari lima puluh orang siswa, baik secara individual maupun dalam kelompok, untuk mengetahui pandangan mereka mengenai bagaimana sekolah mereka mendorong pelaksanaan prinsip keadilan sosial. Artikel ini menemukan bahwa struktur pendidikan di sekolah tersebut, seperti pengelompokan kelas berdasarkan konsentrasi jurusan, pola keberkelompokan siswa, dan munculnya kelas-kelas internasional, menyebabkan ketidakadilan sosial di dalam institusi pendidikan. Siswa kelas Ilmu Sosial dan Bahasa cenderung minim dalam pencapaian akademik, dan secara ekonomi berasal dari kalangan menengah ke bawah. Mereka merasakan bahwa sistem pengelompokan kelas yang berlaku melanggengkan ketidakadilan sosial. Selaras dengan teori reproduksi sosial, sekolah tersebut telah gagal mengimplementasikan keadilan distributif, kultural dan asosiasional, dan bahkan telah melanggengkan ketidakadilan sosial.]